The tyranny of experts : economists, dictators, and the forgotten rights of the poor - Easterly, William, 1957- (Basic Books, a member of the Perseus Book Group, 2013)
Over the last century, global poverty has largely been viewed as a technical problem that merely requires the right "expert" solutions. Yet all too often, experts recommend solutions that fix immediate problems without addressing the systemic political factors that created them in the first place. Further, they produce an accidental collusion with "benevolent autocrats," leaving dictators with yet more power to violate the rights of the poor.